An LRR/Malectin Receptor-Like Kinase Mediates Resistance to Non-adapted and Adapted Powdery Mildew Fungi in Barley and Wheat - Rajaraman, Jeyaraman; Douchkov, Dimitar; Hensel, Götz; Stefanato, Francesca L.; Gordon, Anna; Ereful, Nelzo; Caldararu, Octav F.; Petrescu, Andrei-Jose; Kumlehn, Jochen; Boyd, Lesley A.; Schweizer, Patrick (Frontiers in Plant Science, 2016)
Pattern recognition receptors (PRRs) belonging to the multigene family of receptor-like kinases (RLKs) are the sensing devices of plants for microbe- or pathogen-associated molecular patterns released from microbial organisms. Here we describe Rnr8 (for required for nonhost resistance 8) encoding HvLEMK1, a LRR-malectin domain-containing transmembrane RLK that mediates nonhost resistance of barley to the non-adapted wheat powdery mildew fungus Blumeria graminis f.sp. tritici. Transgenic barley lines with silenced HvLEMK1 allow entry and colony growth of the non-adapted pathogen, although sporulation was reduced and final colony size did not reach that of the adapted barley powdery mildew fungus Blumeria graminis f.sp. hordei. Transient expression of the barley or wheat LEMK1 genes enhanced resistance in wheat to the adapted wheat powdery mildew fungus while expression of the same genes did not protect barley from attack by the barley powdery mildew fungus. The results suggest that HvLEMK1 is a factor mediating nonhost resistance in barley and quantitative host resistance in wheat to the wheat powdery mildew fungus.